2020
DOI: 10.1371/journal.pone.0236465
|View full text |Cite
|
Sign up to set email alerts
|

Time and Covid-19 stress in the lockdown situation: Time free, «Dying» of boredom and sadness

Abstract: A lockdown of people has been used as an efficient public health measure to fight against the exponential spread of the coronavirus disease (Covid-19) and allows the health system to manage the number of patients. The aim of this study (clinicaltrials.gov NCT 0430818) was to evaluate the impact of both perceived stress aroused by Covid-19 and of emotions triggered by the lockdown situation on the individual experience of time. A large sample of the French population responded to a survey on their experience of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
207
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(242 citation statements)
references
References 43 publications
(57 reference statements)
31
207
1
3
Order By: Relevance
“…In addition, our findings showed that the anxiety associated with the virus's effects was also associated with decreased physical health and marital satisfaction. These results are consistent with the findings in the literature on the negative impact associated with stressful events such as the current pandemic (Droit-Volet et al, 2020). Similarly, several studies have also supported the notion that environmental stressors have a negative effect on marital satisfaction (Bodenmann & Randall, 2020;Reizer et al, 2010) and relationship functioning (Reizer et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, our findings showed that the anxiety associated with the virus's effects was also associated with decreased physical health and marital satisfaction. These results are consistent with the findings in the literature on the negative impact associated with stressful events such as the current pandemic (Droit-Volet et al, 2020). Similarly, several studies have also supported the notion that environmental stressors have a negative effect on marital satisfaction (Bodenmann & Randall, 2020;Reizer et al, 2010) and relationship functioning (Reizer et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…For example, patients infected with COVID-19, and even those who were only suspected of being infected, reported increased levels of insomnia (Shigemura et al, 2020). In addition, COVID-19-related stress was found to be associated with increased health complaints among the general French population during a recent lockdown (Droit-Volet et al, 2020). Even among those patients infected with COVID-19, fear of the disease may further amplify the impact of the disease itself (Guan et al, 2020).…”
Section: Fear Of Covid-19 and Perceived Physical Healthmentioning
confidence: 99%
“…The experience of life tedium during the pandemic will play a moderating role in this impact. During the quarantine, many people were restless because of the tedium of life, but many people also found new pleasures, such as cooking or learning a new musical instrument (Droit-Volet et al, 2020). Due to the experience of life tedium greatly improves one's boredom states and sensation-seeking expressions, we suggest that the impulse buying tendency after the pandemic may decrease if an individual's prolonged homestay was filled with new things.…”
Section: Boredom From Limited Activities Sensation-seeking Expressiomentioning
confidence: 87%
“…As stated above, during the pandemic, a high level of perceived severity of COVID-19 made people reluctant to engage with the outside world (Qiu et al, 2020). The long period of physical and psychological limitations severely deprived people of external stimuli, resulting in increased boredom and sensationseeking expressions (Chao et al, 2020;Droit-Volet et al, 2020;Kim, 2020). We suggest that after the COVID-19 pandemic is effectively controlled, people are highly likely to engage in a variety of consumption activities precisely because shopping is a complex stimulus that can relieve consumers' boredom state (Sundström et al, 2019) and satisfy their sensation-seeking needs (Punj, 2011;Deng and Gao, 2015).…”
Section: Boredom From Limited Activities Sensation-seeking Expressiomentioning
confidence: 99%
“…One initial consequence is a profound upheaval in our relationship with time. Recent international surveys on the judgment of the passage of time (PoT) during the lockdown suggested that people have experienced a slowing down of time (Cellini et al, 2020;Droit-Volet et al, 2020;Ogden, 2020;Torboli et al, 2020). However, the different factors explaining this change in the experience of time during lockdown were not further analyzed in these initial surveys, which focused on a limited number of factors (e.g., stress, anxiety, social satisfaction, sleep disturbance).…”
Section: Introductionmentioning
confidence: 99%